ODL: Online Distance Learning of Quantitative Courses in Higher Education - Ghilay, Yaron (Advances in Social Sciences Research Journal, 2017)
The study examined a new asynchronous model for online learning of quantitative courses in higher education, which is a complete substitute for face-to-face learning. The model is called ODL (Online Distance Learning) and is based on a combination of the following successful previous models. 1. CTBL: Comprehensive Technology-Based Learning (Ghilay, 2017). 2. FBL: Feedback Based Learning (Ghilay & Ghilay, 2015a). 3. OTLA: Online Teaching, Learning and Assessment (Ghilay & Ghilay, 2013). The study is based on two samples of students who attended college and participated in an ODL-based course and face-to-face learning of the same course. Students who participated the ODL course, were asked to answer a questionnaire focused on three areas: the course components, characteristics of learning process and time investment. Besides, achievements of the ODL course were compared to the same course in a face to face format. The research reveals that according to students' views, the new model is very helpful for their studying process. Beyond that, it was found that achievements in the ODL course were at least equal to those of a face-to-face course. The results indicate that it is worthwhile to adopt the new model in institutions of higher education.